Toll-Like Receptors Signaling Pathway of Quercetin Regulating Avian Beta-Defensin in the Ileum of Broilers - Ying, Linlin; Wu, Hao; Zhou, Shuaishuai; Lu, Han; Ding, Manyi; Wang, Bo; Wang, Shanshan; Mao, Yanjun; Xiao, Fenglin; Li, Yao (Frontiers in Cell and Developmental Biology, 2022)
The purpose of the experiment was to investigate Toll-like receptor signaling pathway of quercetin regulating avian beta-defensin (AvBD) in ileum of Arbor Acre (AA) broilers.480 one-day-old AA broilers were randomly allotted to 4 treatments, the control treatment and three dietary treatments were fed with the basal diets supplemented with 0, 0.02%, 0.04% and 0.06% quercetin, respectively. The results showed that dietary quercetin supplementation did not significantly influence growth performance (P>0.05), however, significantly decreased the mortality rate by 85.74%, 85.74% and 71.28% of broilers, respectively (P<0.05).Compared with control, dietary supplementation with 0.04% and 0.06% quercetin significantly up-regulated mRNA expression of total AvBD (P<0.05), and there were no significant difference in mRNA expression of AvBD1, AvBD2 and AvBD14 in three quercetin supplementation groups in ileum of AA broilers (P>0.05). Dietary supplementation with 0.02% and 0.06% quercetin significantly down-regulated mRNA expression of total Toll-like receptors (TLRs) (P<0.05). Dietary quercetin supplementation significantly down-regulated mRNA expression of TLR1A, TLR1B, and TLR2A (P<0.05), however, there were no significant difference in mRNA expression of TLR2B, TLR5 and TLR15 (P>0.05). Dietary quercetin supplementation significantly down-regulated mRNA expression of myeloid differentiation primary response protein 88 (MyD88) and TIR domain containing adaptor protein/MyD88-adaptor-like (TIRAP/MAL) (P<0.05), 0.02% quercetin significantly down-regulated mRNA expression of tank-binding kinase1 (TBK1), IκB kinase complex-α (IKKα), IKKβ, IKKε, nuclear factor-kappa B (NF-κB), NF-κB inhibitor-alpha (IκBα), IκBα, IκBβ, TNF-receptor-associated factor 3 (TRAF3) and interferons regulatory factor 7 (IRF7) (P<0.05); 0.04% quercetin significantly down-regulated mRNA expression of IKKβ, IKKε, NF-κB, IκBα, IκBβ, TRAF3 and TRAF6 (P<0.05), 0.06% quercetin significantly down-regulated mRNA expression of TBK1 and IKKα (P<0.05). 0.02% quercetin significantly decreased relative abundance of Escherichia, Staphylococcus (P<0.05) and Salmonella (P<0.01), 0.04% quercetin significantly decreased relative abundance of Staphylococcus (P<0.05), Escherichia and Salmonella (P<0.01), 0.06% quercetin significantly decreased relative abundance of Salmonella (P<0.05) and Staphylococcus (P<0.01) in ileum of AA broilers. These findings suggested that dietary quercetin supplementation regulated mRNA expression of AvBD, TLR and the TLR and NF-κB signaling pathways,thereby maintaining the micro-ecological balance of the intestinal tract and decreasing mortality of broilers, and the optimum addition amount of quercetin is 0.04% under the test conditions.